Comparison of the effectiveness of a structured exercise program on nonspecific neck pain in string and woodwind players - Usgu, Serkan; Akbey, Hasan; Kocyigit, Burhan Fatih; Akyol, Ahmet; Yakut, Yavuz (Springer Heidelberg, 2022)
To investigate the effect of a structured exercise training program on pain, functional status, physical function and quality of life (QoL) in string and woodwind players with nonspecific cervical pain. This study had a prospective cohort design and conducted on 40 musicians (26 male, 14 female) aged between 18 and 65 years with persistent nonspecific neck pain in the previous 3 months. Forty musicians were assigned to either violin (n = 20, median age; 26.5 year, height; 1.67 m, body mass; 65 kg, BMI; 23.04 kg/m(2)) or ney group (n = 20, median age; 27.5 year, height; 1.81 m, body mass; 75 kg, BMI; 23.35 kg/m(2)) and followed the same structured exercise program (3 days/per week for 8 weeks). The primary outcome was neck pain intensity and assessed on a visual analog scale (VAS). Secondary outcomes; cervical range of motion (ROM) was measured using a goniometer, the jaw-to-sternum and jaw-to-wall distances were used for the assessment of cervical mobility, neck, shoulder and back muscles strength were assessed with a hand-held dynamometer, the Northwick Park Neck Pain and Short Form 36 (SF-36) questionnaires were also used. Normality of data distribution was checked using the Kolmogorov-Smirnov test. For evaluating the training effectiveness on outcome measures, Mann-Whitney U and Wilcoxon test were used compare pre-test and post-test values with/within groups, respectively. The primary outcome (pain intensity) was lowered %33 in both groups. However, the mean change was found similar (median mean changes; -2 for both groups) (p > 0.05). The secondary outcomes; cervical mobility, cervical flexion ROM, disability and muscle strength of the left middle trapezius, left hand grip, anterior and middle parts of the right deltoid, and cervical flexors also significantly improved in both groups (p < 0.05). Only the mean changes of right serratus anterior, middle trapezius and cervical flexor muscles were higher in violin group than ney group (p < 0.05). There was no significant difference in the cervical extension, right rotation, left rotation, right lateral flexion and left lateral flexion after the treatment in both groups (p > 0.05). There was no significant difference between the groups after the exercise program in terms of pain, mobility, range of motion and SF-36 subdomains (p > 0.05). Specific exercise program had similar positive effects on pain, cervical mobility, cervical fexion ROM and disability in string and woodwind players. Although several muscles showed similar improvements in strength, some muscle groups recovered differently. Physical needs specific to the instrument and performance should be taken into account when prescribing exercises to musicians having the same problem, but playing different instruments.
Keywords: Exercise; Neck pain; Disability; Musicians; Rehabilitation